If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 4x + -2 = 0 Reorder the terms: -2 + 4x + y = 0 Solving -2 + 4x + y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 4x + 2 + y = 0 + 2 Reorder the terms: -2 + 2 + 4x + y = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 4x + y = 0 + 2 4x + y = 0 + 2 Combine like terms: 0 + 2 = 2 4x + y = 2 Add '-1y' to each side of the equation. 4x + y + -1y = 2 + -1y Combine like terms: y + -1y = 0 4x + 0 = 2 + -1y 4x = 2 + -1y Divide each side by '4'. x = 0.5 + -0.25y Simplifying x = 0.5 + -0.25y
| -6x-10=19-5x | | 13+x=-20 | | 3*4.5-y=9 | | 2x^2+3y^2+12x-12y-210=0 | | 7(2x+9)=3x+100 | | 6+3*5-2=18 | | 5(3x-6)=12 | | 19=23-2v | | -2(4x-2)+6x=4(x+3) | | 4m-9= | | 6+3*5-2=5 | | 2(3x+2)+6(2x-1)=40 | | 13x-4=2x+4 | | -72=-8(4-2x)-8(1-2x) | | 13x-4=2x+2 | | 2p=96-10 | | 5p-7p=3p+1 | | 13x+4=-5x+1 | | -86=-2(1-6a) | | 6sqrtx=x | | -5(-3v+5)-8v=3(v-5)-4 | | 13x+4=-5x-3 | | 2m+3m=4m-9 | | 4(2x-5)=43 | | -37=-3(1+6m)-2(m+7) | | 3m^3-15m^2+75m=0 | | x^2+y^2-22x+112=0 | | 2b-5b=-9 | | (2x-1)/4+(3x+4)/8=(1-4x)/12 | | 3(z+3)=2(z+8) | | 31=5x+5x-9 | | 9-ln(4-x)=0 |